Protostars and planets VI - Beuther, Henrik; Klessen, Ralf S.; Dullemond, Cornelis; Henning, Thomas (The University of Arizona Press, 2014)
"This volume integrates the cross-disciplinary aspects of this broad field. Covering a wide range of scales, from the formation of large clouds in our Milky Way galaxy down to small chondrules in our solar system, it takes an encompassing view with the goal of highlighting what we know and emphasizing the frontiers of what we do not know"--Provided by publisher
Proceedings of a conference held in Heidelberg, Germany, July 15 - 20, 2013. - Includes bibliographical references and index
Keywords: Konferenzschrift -- 2013 -- Heidelberg; Sternentstehung